FAKTOR-FAKTOR PENENTU STRUKTUR MODAL PADA PERUSAHAAN SUB SEKTOR FARMASI - Safitri, Ramdana; Hendra, Hendra (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this research is to obtain empirical evidence regarding the impact of Profitability, Company Size, Sales Growth, Liquidity and Asset Structure on Capital Structure in Pharmaceutical Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2011-2020 period. The research sample used was 7 companies and 70 data, and the sample selection procedure was carried out using purposive sampling method. The data were analyzed using descriptive statistics and regression panel with a FEM model to testing all hypotheses. The research shows that if the profitability and sales growth has a positive effect on capital structure compliance, because the higher profit and sales will give secure collateral to creditor. Then liquidity has a negative effect on capital structure because if company has a good liquidity, they usually don’t need so much debt. Furthermore, the variables of firm size and asset structure have no effect on the capital structure.